Shoe town - Stevens, Janet; Stevens, Janet (Florida : Harcourt, 2000)
As she tries to settle down for a nap, a mouse who lives in a shoe is visited first by Tortoise and Hare, then by Little Red Hen, and lastly by the Big Bad Wolf.
Keywords: Mice -- Fiction; Shoes -- Fiction; Stories in rhyme; Reading training, English (Elementary).